2018
DOI: 10.1111/ppl.12861
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of strawberry (Fragaria × ananassa) fruits under osmotic stresses and identification of genes related to ascorbic acid pathway

Abstract: Strawberry (Fragaria ananassa Duch.) is an economically important fruit with a high demand owing to its good taste and medicinal properties. However, its cultivation is affected by various biotic and abiotic stresses. Plants exhibit several intrinsic mechanisms to deal with stresses. In the case of strawberry, the mechanisms highlighting the response against these stresses remain to be elucidated, which has hampered the efforts to develop and cultivate strawberry plants with high yield and quality. Although a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…As one kind of delicious and nutritive fruit, strawberry is very popular in the fresh fruit market worldwide (Feng et al , Galli et al ). It has been reputed as the ‘fruit queen’.…”
Section: Introductionmentioning
confidence: 99%
“…As one kind of delicious and nutritive fruit, strawberry is very popular in the fresh fruit market worldwide (Feng et al , Galli et al ). It has been reputed as the ‘fruit queen’.…”
Section: Introductionmentioning
confidence: 99%
“…Among abiotic stressors, drought and salt stress, caused by excess Na + and Cl − ions, are the most limiting factors impacting plant growth, development, and survival. Under extreme drought and salt stress, plants respond by changing the expression of some stress‐related genes affecting physiological aspects, leading to reduced yield and biomass . However, recent studies indicate that moderate stress may serve as an effective biofortification strategy to improve the functional quality of fruits without a significant reduction in yield …”
Section: Introductionmentioning
confidence: 99%
“…Under extreme drought and salt stress, plants respond by changing the expression of some stress-related genes affecting physiological aspects, leading to reduced yield and biomass. [1][2][3] However, recent studies indicate that moderate stress may serve as an effective biofortification strategy to improve the functional quality of fruits without a significant reduction in yield. 4,5 General metabolites such as carbohydrates, fatty acids, proteins, and nucleic acids are synthesized by all plant species and play fundamental roles in the plant's life cycle and growth.…”
Section: Introductionmentioning
confidence: 99%
“…ABA content was also observed to increase in strawberry fruits under saline and drought stresses; however, ABA biosynthesis related genes (FaNCEDs, FaCYP707As, FaGTs, and FaBGs) were mostly upregulated only in drought stressed fruits 25 . Similarly, only the drought stress increased the concentrations of ascorbic acid, sugars, and methylsyringin, whereas salt stress induced the synthesis of amino acids in the fruits 26,70 . A mechanism of salt and drought response in strawberry fruits based on these previous results and the gene expression data from this study is shown in Fig.…”
Section: Discussionmentioning
confidence: 95%